Nephrotic Syndrome Secondary to Proliferative Glomerulonephritis with Monoclonal Immunoglobulin Deposits of Lambda Light Chain - Seongseok Yun; Beth L. Braunhut; Courtney N. Walker; Waheed Bhati; Amy N. Sussman; Faiz Anwer (Case Reports in Nephrology)
We describe a rare case of a 46-year-old woman with history of refractory nephrotic syndrome and hypertension who presented with worsening proteinuria and kidney function. Work-up for both autoimmune and infectious diseases and hematologic malignancies including multiple myeloma were negative. Kidney biopsy demonstrated glomerular sclerotic change with lambda light chain deposits in the subendothelial space, which is consistent with proliferative glomerulonephritis with monoclonal immunoglobulin deposit (PGNMID). The patient was treated with bortezomib and dexamethasone without clinical improvement and eventually became hemodialysis dependent.